Possibilities of pulsation measurements in the Ecuadorian ocean/fishery ecosystem affecting by the Humboldt Current derived from the Antarctic Ocean - Naganobu, Mikio (2019)
The Tenth Symposium on Polar Science/Ordinary sessions : [OB] Polar Biology, Wed. 4 Dec. / Entrance Hall (1st floor) , National Institute of Polar Research conference object